Three-Dimensional Modeling of the Pelvic Floor Support Systems of Subjects with and without Pelvic Organ Prolapse. - Ren, Shuang; Xie, Bing; Wang, Jianliu; Rong, Qiguo (BioMed Research International, 2015)
The purpose of this study was to develop three-dimensional finite element models of the whole pelvic support systems of subjects with and without pelvic organ prolapse (POP) that can be used to simulate anterior and posterior wall prolapses. Magnetic resonance imaging was performed in one healthy female volunteer (55 years old, para 2) and one patient (56 years old, para 1) with anterior vaginal wall prolapse. Contours of the pelvic structures were traced by a trained gynecologist. Smoothing of the models was conducted and attachments among structures were established. Finite element models of the pelvic support system with anatomic details were established for both the healthy subject and the POP patient. The models include the uterus, vagina with cavity, cardinal and uterosacral ligaments, levator ani muscle, rectum, bladder, perineal body, pelvis, obturator internus, and coccygeal muscle. Major improvements were provided in the modeling of the supporting ligaments and the vagina with high anatomic precision. These anatomically accurate models can be expected to allow study of the mechanism of POP in more realistic physiological conditions. The resulting knowledge may provide theoretical help for clinical prevention and treatment of POP.